2018
DOI: 10.1111/hae.13616
|View full text |Cite
|
Sign up to set email alerts
|

Treatment regimens and outcomes in severe and moderate haemophilia A in the UK: The THUNDER study

Abstract: Introduction The THUNDER study provides an analysis of treatment patterns and outcomes in UK patients with severe or moderate haemophilia A (SHA/MHA) in 2015. Methods Patients with SHA or MHA registered with the UK National Haemophilia Database (NHD) were segregated by severity, inhibitor status and age. Haemophilia joint health score (HJHS) was derived from NHD records and treatment regimen and annualized bleed/joint‐bleed rate (ABR/AJBR) from Haemtrack (HT) in HT‐compliant patients. Results We report 1810 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
126
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(137 citation statements)
references
References 31 publications
5
126
2
4
Order By: Relevance
“…In both studies, however, there was a gap of several years between age at first joint bleed and start of prophylaxis. In severe haemophilia, age at start of prophylaxis has been found as an independent predictor for development of arthrop- Compared with the THUNDER study from the UK, 6 we report a lower prevalence of prophylaxis than among their subgroup with MHA (38% vs 69%). Still, their bleeding frequency was high with median two (prophylaxis) and five annual joint bleeds (on-demand).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In both studies, however, there was a gap of several years between age at first joint bleed and start of prophylaxis. In severe haemophilia, age at start of prophylaxis has been found as an independent predictor for development of arthrop- Compared with the THUNDER study from the UK, 6 we report a lower prevalence of prophylaxis than among their subgroup with MHA (38% vs 69%). Still, their bleeding frequency was high with median two (prophylaxis) and five annual joint bleeds (on-demand).…”
Section: Discussioncontrasting
confidence: 75%
“…More recently, the THUNDER study reported high bleeding rates among patients with moderate haemophilia A in the UK. 6 Haemophilia A and B have usually been considered as indistinguishable diagnoses, but there are data suggesting that patients with severe haemophilia B have a less severe bleeding phenotype. 7,8 Data comparing the clinical phenotypes in moderate haemophilia A (MHA) and B (MHB), however, are scarce with no clear difference between them.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence indicates that despite prophylaxis, boys with severe and moderate haemophilia still bleed one to two times per year. 1 It is well established that muscle weakness is associated with haemophilic arthropathy in adults 2 and it is now becoming apparent that muscle strength may be reduced in children, prior to the onset of clinical arthropathy. 3,4 Therapeutic exercise is an important component of the management of other forms of arthropathy (eg osteoarthritis and rheumatoid arthritis), 5 and it would appear logical that exercise would be effective for people with haemophilia.…”
Section: Dear Editormentioning
confidence: 99%
“…1 In particular, patients with a residual factor VIII (FVIII) activity of 1%-5% may have frequent spontaneous bleeds that may also be clinically severe. 2,3 The superiority of prophylactic FVIII replacement over on-demand treatment has been demonstrated for severe HA. 1,4,5 Starting a primary prophylaxis in children with severe HA can wholly or largely prevent life-threatening bleeds, chronic arthropathy and disability, thereby reducing the need for surgical interventions and contributing to improved health and social well-being for HA patients.…”
Section: Introductionmentioning
confidence: 99%